Benefits of Authentic Education with Multidisciplinary Perspectives from the Viewpoints of Analytical Psychology - Watagodakumbura, Chandana (Advances in Social Sciences Research Journal, 2014)
Authentic education system highlighted in this paper provides a unique learning experience to individual learners, specifically by addressing their psychological and neurological needs; assessment of learners are done through generic attributes that have more validity and relates to intrinsic learner characteristics, lasting throughout the life span. The psychological types or conscious functions defined in analytical psychology provide additional insights into learner classification and identifying appropriate generic attributes. . In the authentic education system described, learners are encouraged to pursue higher-order learning sending them through a complete learning cycle; this engages learners deeply to the task and provides a lasting experience, enabling individuals to reach their full potential. Learners are encouraged to pursue an individuation process as described in analytical psychology towards a higher level of human development; that is the shadow or the inferior functions are directly addressed enabling the path towards the concept of the self. Through authentic education, we get to value human resources much more than related economic aspects, making a significant difference to our current approaches and focus; it has the promise to effect a significant positive social change towards a sustainable development. In this regard, the viewpoints from analytical psychology as a framework of human development provide additional justifications.